Motorcycle Ban and Traffic Safety: Evidence from a Quasi-Experiment at Zhejiang, China - Jingjing Chen; Qian Wang; Jie Huang (Journal of Advanced Transportation)
Motorcycle bans have been implemented in many cities across China for long time, one of the main reasons for which is the high death rate of the traffic accidents related to motorcycles’ fast speed and weak safety. This study applies a quasi-experiment on whether or not and when motorcycle bans are implemented in the 11 prefecture cities in Zhejiang Province, taking the prefecture-level cities with motorcycle bans as the experimental group and the others as the control group, so as to identify whether such bans can effectively reduce the number of traffic accidents and deaths, as well as the related internal mechanism. This study concludes that the effect of the motorcycle bans on reducing the number of traffic accident deaths is significant, and their impact does not decrease over time due to the diversity of policies. Further, the mechanism analysis shows that the motorcycle bans have not only reduced the number of motorcycles and thus may improve the traffic safety but also diminished the traffic accidents by reducing the fatality rate. Finally, this study proposes to optimize the motorcycle bans by planning special lanes and strengthening motorcycle management.